2015
DOI: 10.1002/ange.201501818
|View full text |Cite
|
Sign up to set email alerts
|

Das Bindeglied zwischen Bisyliden und Methandiiden: Isolierung, Reaktivität und elektronische Struktur eines Yldiids

Abstract: Bisylide und Methandiide stellen aufgrund ihrer elektronischen Struktur zwei besondere Klassen von Kohlenstoffbasen dar, die in den letzten Jahren eine Vielzahl an Anwendungen gefunden haben. Metallierte Ylide (Yldiide) sind das Bindeglied zwischen beiden Verbindungsklassen. Über ihre Eigenschaften, Reaktivitäten und besonders über ihre elektronische Struktur ist jedoch bis heute nur wenig bekannt. Hier berichten wir über die Synthese des metallierten Ylids [Ph3P‐C‐SO2Tol]− (1) mit verschiedenen Alkalimetall‐G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…[7] These compounds also exhibit two lone pairs of electrons at the central ylidic carbon atom and are thus strong donor ligands, which, for example, allowedt he stabilization of as eries of borenium ions or the synthesis of highly electron-rich phosphine ligands. [8,9] Despite their huge synthetic potential, very little is knowna bout their electronic structures. Only four yldiides have been isolated and structurally authenticated so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] These compounds also exhibit two lone pairs of electrons at the central ylidic carbon atom and are thus strong donor ligands, which, for example, allowedt he stabilization of as eries of borenium ions or the synthesis of highly electron-rich phosphine ligands. [8,9] Despite their huge synthetic potential, very little is knowna bout their electronic structures. Only four yldiides have been isolated and structurally authenticated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Only four yldiides have been isolated and structurally authenticated so far. [8,10] In this regard, yldiide 1 seemed to be especially interesting because it can be viewed as an anionic carbone, in which the carbona tom is coordinated like am etal in ac yanido-phosphine complex (Figure 1). Thus, comparable to bisylides, the yldiide may exhibit different bondings ituations, which also may be influenced by the counter cation (typically M + + with M = Li, Na, or K).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with ar educed negative charge at C1 and reduced electrostatic interactions within the P À C À Sb ackbone,w hich is conform with the p-interaction between the ylide ligand and the boron center. [15] NMR spectroscopic studies of 2 revealed that the structure observed in solid-state is also preserved in solution. As such, dichloromethane (DCM) solutions of 2 showedindependent of the counter-anion-only as ingle broadened peak in the 31 P{ 1 H} NMR spectrum at d P = 12.5 ppm as well as broadened signals in the 1 Ha nd 13 CNMR spectra at room temperature.T his is consistent with ad ynamic behavior and the alternating coordination of one of the two sulfonyl moieties to boron.…”
mentioning
confidence: 99%
“…Our group has become interested in the coordination chemistry of ylidic donor ligands.P articularly,m etalated ylides with two lone pairs of electrons at the central carbon atom seemed to be ideal ligands for the stabilization of electron-deficient species due to their potential ability to function as carbon-centered sand p-donor ligands. [15] Herein, we challenged this donor capacity of metalated ylides and their applicability as anovel class of X,L-type ligands for the stabilization of cationic boron species.…”
mentioning
confidence: 99%
See 1 more Smart Citation